The Characterization of Almost Prime Submodule on the Finitely Generated Module over Principal Ideal Domain - Wardhana, I Gede Adhitya Wisnu; Astuti, Pudji; Muchtadi-Alamsyah, Intan (IndoMS, 2024)
In most cases, almost prime submodules are equivalent to prime submodules, but in a finitely generated module, it is not necessarily equivalent. Based on the fact that a finitely generated module over a principal ideal domain can be decomposed into a free part and a torsion part, we give a new approach to the characteristic of almost prime submodules in the finitely generated module, especially we point out the cases when the submodules are almost prime but not prime.